Efficient Inverted ITO-Free Organic Solar Cells Based on Transparent Silver Electrode with Aqueous Solution-Processed ZnO Interlayer - Zhizhe Wang; Dazheng Chen; Chunfu Zhang; Zhenhua Lin; Yan Liu; Genquan Han; Jingjing Chang; Jincheng Zhang; Lixin Guo; Yue Hao (International Journal of Photoenergy)
Efficient inverted organic solar cells (OSCs) with the MoO3 (2 nm)/Ag (12 nm) transparent cathode and an aqueous solution ZnO electron extraction layer processed at low temperature are investigated in this work. The blend of low bandgap poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7) and [6,6]-phenyl-C71-butyric acid methylester (PC71BM) is employed as the photoactive layer here. A power conversion efficiency (PCE) of 5.55% is achieved for such indium tin oxide- (ITO-) free OSCs under AM 1.5G simulated illumination, comparable to that of ITO-based reference OSCs (PCE of 6.11%). It is found that this ZnO interlayer not only slightly enhances the transparency of MoO3/Ag cathode but also obtains a lower root-mean-square (RMS) roughness on the MoO3/Ag surface. Meanwhile, ITO-free OSCs also show a good stability. The PCE of the devices still remains above 85% of the original values after 30 days, which is slightly superior to ITO-based reference OSCs where the 16% degradation in PCE is observed after 30 days. It may be instructive for further research of OSCs based on metal thin film electrodes.